2021
DOI: 10.12788/jhm.3667
|View full text |Cite
|
Sign up to set email alerts
|

Racial and Ethnic Disparities in Discharge Opioid Prescribing From a Hospital Medicine Service

Abstract: BACKGROUND: Differential opioid prescribing patterns have been reported in non-White patient populations. However, these disparities have not been well described among hospitalized medical inpatients. OBJECTIVE: To describe differences in opioid prescribing patterns among inpatients discharged from the general medicine service based on race/ethnicity. DESIGN, SETTING, AND PARTICIPANTS: For this retrospective study, we performed a multivariable logistic regression for patient race/ethnicity and whether patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 38 publications
(83 reference statements)
0
16
0
Order By: Relevance
“…There have been a multitude of studies describing racial disparities in pain management. 14,15 Our study showed decreased odds of OSS use in African American patients compared to Caucasian on univariate analysis. This also shows a potential area for improvement throughout the state.…”
Section: Discussionmentioning
confidence: 68%
“…There have been a multitude of studies describing racial disparities in pain management. 14,15 Our study showed decreased odds of OSS use in African American patients compared to Caucasian on univariate analysis. This also shows a potential area for improvement throughout the state.…”
Section: Discussionmentioning
confidence: 68%
“…Indeed, patient characteristics such as geographic location, race, and type of insurance have been shown to influence opioid prescribing habits [14,34]. Multiple studies have demonstrated that adults who are non-White are less likely to receive opioids for pain control than adults who are White [1,16,20,21,32]. However, there is a lack of research into the association of race and opioid prescribing in the pediatric population.…”
Section: Introductionmentioning
confidence: 99%
“…R acial disparities in opioid prescribing patterns in United States healthcare delivery systems have been well described for many years [10]. Numerous studies have demonstrated lower rates of opioid prescriptions for Black and Hispanic patients than for their White counterparts across several healthcare contexts, including the emergency department [13,17], inpatient medicine [14], general surgery [8], and outpatient chronic pain management [15].…”
mentioning
confidence: 99%